Not Much Bounce in the Springboard: On the Mobility of Low Pay Workers - Gail Pacheco; Alexander T. Plum; Peter J. Sloane (Institute of Labor Economics (IZA), 2020)
Estimating economic earnings mobility is imperative for understanding the degree to which low pay employment is a temporary or long-term position. The current literature estimates transition probabilities between low and higher pay. This study extends the focus to identify the underlying pecuniary wage change via construction of an intermediate pay zone marginally above low pay. Utilising monthly administrative data we find that individuals with a strong attachment to the low pay sector have a very low probability of shifting into higher pay. Further, these individuals also have a substantially greater risk of experiencing a low pay-no pay cycle relative to those who are intermediate or higher paid. Notably, this finding is only uncovered using within year variation in wages to reveal intensity of labour market attachment.
Keywords: J62; J31; C33; C55; 330; low pay dynamics; transition probability; state dependence; dynamic models; administrative data